DESCRIPTIVE STUDY OF CURRICULUM DEVELOPMENT AND PAI LEARNING MODELS AT LKP EL RAHMA EDUCATION CENTER - Wendy Asswan Cahyadi; Siti Qomariyah (SEAN Institute, 2022)
The inability of graduates to keep pace with world industrial and technological developments is the cause of the accumulation of the workforce in sectors that do not require higher skills and education. In addition, Islamic education (PAI) is often considered an unimportant subject in vocational education. Islamic religious education is not given the proper portion, even though the ages of vocational education students are those who are able to think and process personality formation. The purpose of this research is to develop the implementation of curriculum development and PAI learning model. This study uses a descriptive study method with a qualitative approach. Data collection techniques in this study using interviews, observation and documentation. The research was conducted at the El Rahma Education Center Course & Training Institute, Bogor City. This study concludes that the curriculum and learning model of PAI developed must be short, interesting, but very touching to the mind and heart so that it has an effect on significant behavioral changes according to Islamic teachings